Implementation Employee Well-Being: Analysis Leadership Agility, Workload Analysis, Organizational Culture, and Career Adaptability - Emmy Junianti; Zahara Tussoleha Rony (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee well-being is an important issue that must be considered by the Human Resources Development department in every organization to be able to maximize employee performance and optimize organizational achievement. This research was conducted using a systematic literature review with sources from various journal publishers. The independent variables examined in this study are Leadership Agility, Workload, Organizational culture, and Career Adaptability. The results and this research show that the implementation of Employee well-being can be achieved if an organization has an agile leader, can analyze the ideal workload, has a positive work culture and has employees with good career adaptability. Suggestions for further research are to take data directly from the field so that the research results become more valid.